THE EFFECT OF TOPICAL TOMAN (Channa micropeltes) FISH EXTRACT ON THE NUMBER OF NEUTROFIL CELLS IN DIABETES MELITUS WOUND HEALING (In Vivo Study on Male Wistar (Rattus novergicus) Rat’s Back) - Annisa Vara Nurdianty; Maharani Laillyza Apriasari; Amy Nindia Carabelly (Dentino : Jurnal Kedokteran Gigi, 2019)
Backgrounds: Diabetes mellitus forges the wound healing process to last longer. Toman fish which contains albumin and omega-6 fatty acid is proven to to enhance wound healing process in this systemic condition. Patients who suffer from diabetes mellitus retain high neutrophil number. Omega-6 fatty acids contained in Toman fish can decrease the number of  neutrophil cells. Objectives:  To prove the effect of Toman fish (Channa micropeltes) extract at 20% concentration topically on the number of neutrophil in diabetes mellitus-induced Wistar Rat (Rattus novergicus) injuries on day 4, 8 and 14.  Methods: This research was a true experimental study with posttest-only and control group with complete random design. Thirty six male Wistar rats (Rattus novergicus) was divided evenly for three treatments comprised of negative control given BR2 comfeed, positive control treated with Haruan fish (Channa striata) extraxt at 10% concentration topically and treatment group given with Toman fish (Channa micropeltes) extract at 20% concentration topically. Results: The data was analyzed using One Way ANOVA and was presenting the result of the 4th day (p=0.000), 8th day (p=0.001) and 14th day (p=0.000). Post-hoc Least Significant Difference (LSD) showed that p value was less than 0.05 which means that there was a significance difference in the mean of all treatment groups. Conclusion: Toman fish (Channa micropeltes) extract possesses the capacity in decreasing the number of neutrophil on 4th, 8th and 14th day in diabetic wound healing of Wistar Rat (Rattus novergicus).